Telephone clinic outcomes during the coronavirus disease 2019 pandemic: results from an ENT department. Issue 7 (16th July 2022) - Mallick, S; Balakumar, R; Drysdale, A
Abstract: Objective: To study the impact of telemedicine on patient outcomes during a nationwide lockdown to halt the spread of coronavirus disease 2019. Methods: A retrospective study was conducted to examine telemedicine consultations of newly referred patients over 7 days during a national lockdown. Overall outcomes of telephone clinics were recorded, measured as either patient discharged, imaging requested, patient referred to another specialty, further telephone follow up required, patient initiated follow up or face-to-face appointment required. Results: Data were collected from 104 patients. Outcomes showed that 17 patients were discharged, 15 had imaging requested, 11 were referred to another specialty, 11 had further telemedicine appointments, 31 had patient-initiated follow up and 19 received face-to-face appointments. Overall, 57 per cent of patients avoided hospital visits and 17 per cent required face-to-face appointments. Of higher risk patients, 49 per cent were managed remotely. After eight months, no significant morbidity or mortality was reported. Conclusion: Almost half of the higher risk patients avoided a hospital visit. The majority of patients were managed remotely, and thus the risk and spread of infection were reduced. Telemedicine has an important role in ENT out-patients.